Revitalising soil health through the Africa Fertilizer and Soil Health Action Plan - African Union Development Agency-NEPAD; Accelerating Impacts of CGIAR Climate Research for Africa (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
This poster introduces the African Union's Africa Fertilizer and Soil Health (AFSH) Action Plan (2024 - 2034) which aims to improve soil health in Africa for enhanced agricultural productivity, increased food security and poverty alleviation. It provides the outcomes and action areas from the AFSH Action Plan that specifically target soil health. Some of the key action areas include an improved policy environment, improved finance and investments, targeted soil health interventions, increased networking and knowledge exchange, and improved institutional and human capacity for sustainable soil health.